2022
DOI: 10.1186/s12915-022-01421-0
|View full text |Cite|
|
Sign up to set email alerts
|

Lineage-specific, fast-evolving GATA-like gene regulates zygotic gene activation to promote endoderm specification and pattern formation in the Theridiidae spider

Abstract: Background The process of early development varies across the species-rich phylum Arthropoda. Owing to the limited research strategies for dissecting lineage-specific processes of development in arthropods, little is known about the variations in early arthropod development at molecular resolution. The Theridiidae spider, Parasteatoda tepidariorum, has its genome sequenced and could potentially contribute to dissecting early embryonic processes. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 122 publications
0
4
0
Order By: Relevance
“…Increasing animal genomic information and annotations have revealed the existence of lineage-specific, fast-evolving transcription factors (Holland et al, 2017). Recent studies have reported several lineage-specific transcription factors that show zygotic expression during early development (Dylus et al, 2016;Ferguson et al, 2014;Iwasaki-Yokozawa et al, 2022;Lewin et al, 2021Lewin et al, , 2022Maeso et al, 2016;Yamazaki et al, 2020). In spiralians, many lineage-specific transcription factors are also known to exhibit peak expression during the early cleavage stages (Paps et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing animal genomic information and annotations have revealed the existence of lineage-specific, fast-evolving transcription factors (Holland et al, 2017). Recent studies have reported several lineage-specific transcription factors that show zygotic expression during early development (Dylus et al, 2016;Ferguson et al, 2014;Iwasaki-Yokozawa et al, 2022;Lewin et al, 2021Lewin et al, , 2022Maeso et al, 2016;Yamazaki et al, 2020). In spiralians, many lineage-specific transcription factors are also known to exhibit peak expression during the early cleavage stages (Paps et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although the developmental toolkit genes were once thought to be largely conserved among animals, recent genomic studies and curated annotations have revealed that lineage-specific and fast-evolving transcription factors are expressed during animal development (Holland et al, 2017), including in mammals (Lewin et al, 2021(Lewin et al, , 2022Maeso et al, 2016), echinoderms (Dylus et al, 2016;Yamazaki et al, 2020), lepidopterans (Chai et al, 2008;Ferguson et al, 2014;Mulhair et al, 2023), spiders (Iwasaki-Yokozawa et al, 2022), and spiralians (Morino, 2022;Morino et al, 2017;Paps et al, 2015;Phuangphong et al, 2021). In the examples above, most transcription factors are expressed zygotically and function early in animal development.…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate genes (and thus gene regulatory networks) beyond the classic candidate gene approach, genomics and embryonic and tissue-specific transcriptomics have been applied in the recent past, leading to the investigation of complete gene families, orphan genes, fast evolving genes and tissue-specific genes (e.g. [ 20 , 77 , 89 , 142 , 155 ]. A relatively recent new technical innovation now allows investigation of the transcriptome of every cell of a given organism or a developmental stage of a given organism separately.…”
Section: Introductionmentioning
confidence: 99%
“…The original article [ 1 ] erroneously presented the supplementary materials in accordance with their respective citations; the supplementary files are now correctly presented and cited.…”
mentioning
confidence: 99%